Implementasi Literasi Baca Tulis dan Numerasi untuk meningkatkan Rapor Pendidikan di SMK NU Miftahul Falah Kudus - Afif, Moh. Noor; Bunyamin, Bunyamin; Maryanto, Maryanto (MODELING: Jurnal Program Studi PGMI, 2025)
This research is motivated by the importance of the school literacy movement (GLS) in improving students' reading culture based on the reason that many students are less enthusiastic about reading which ultimately aims to improve the education report at SMK NU Miftahul Falah Kudus. The purpose of this study is to describe and analyze the Planning, Implementation and Evaluation of reading, writing and numeracy literacy to improve the education report at SMK NU Miftahul Falah Kudus. The research approach used is descriptive qualitative. This research was conducted at SMK NU Miftahul Falah Kudus which was implemented from October 2024 to February 2025. The subjects of the study were grade XI students at SMK NU Miftahul Falah Kudus. The research informants were the Principal, Deputy Head of Curriculum Affairs, Teachers and students. The research data was obtained through observation, interviews, tests and documentation. Checking the validity of the data using technical triangulation. Data analysis with data collection, data reduction, data presentation and conclusions. The results of the study indicate that: 1) GLS planning at SMK NU Miftahul Falah Kudus Overall has been well planned. However, the researcher considers the need for planning such as completing the library book collection in the coming year. 2) The implementation of GLS at SMK NU Miftahul Falah Kudus has been in accordance with the GLS guidelines, namely by holding socialization, providing materials, teacher guides in class guiding, motivating, providing reinforcement in communicating the objectives of the GLS program, summarizing to providing assessments 3) Evaluation of GLS at SMK NU Miftahul Falah Kudus It can be concluded that the literacy program at SMK NU Miftahul Falah Kudus was successful enough so that this program can be continued by improving some of its weaknesses so that it can be applied elsewhere.